Testin regulates the blood‐testis barrier via disturbing occludin/ZO‐1 association and actin organization. Issue 9 (24th January 2020) - Su, Linlin; Wang, Zhaohua; Xie, Songtao; Hu, Dahai; Cheng, Yan C.; Mruk, Dolores D.; Guan, Yongjun
Abstract: The blood‐testis barrier (BTB) separates the seminiferous epithelium into the apical and basal compartments. The BTB has to operate timely and accurately to ensure the correct migration of germ cells, meanwhile maintaining the immunological barrier. Testin was first characterized from primary Sertoli cells, it is a secretory protein and a sensitive biomarker to monitor junctions between Sertoli and germ cells. Till now, the functions of testin on BTB dynamics and the involving mechanisms are unknown. Herein, testin acts as a regulatory protein on BTB integrity. In vitro testin knockdown by RNAi caused significant damage to the Sertoli cell barrier with no apparent changes in the protein levels of several major tight junction (TJ), adhesion junction, and gap junction proteins. Also, testin RNAi caused the diffusion of two TJ structural proteins, occludin and ZO‐1, diffusing away from the Sertoli cell surface into the cytoplasm. Association and colocalization between ZO‐1 and occludin were decreased after testin RNAi, examined by Co‐IP and coimmunofluorescent staining, respectively. Furthermore, testin RNAi induced a dramatic disruption on the arrangement of actin filament bundles and a reduced F‐actin/G‐actin ratio. The actin regulatory protein ARP3 appeared at the Sertoli cell interface after testin RNAi without its protein level change, whereas overexpressing testin in Sertoli cells showed no effect on TJ barrier integrity. The above findings suggest that besides as a monitor for Sertoli‐germ cell junction integrity, testin is also an essential molecule to maintain Sertoli–Sertoli junctions. Abstract : Testin regulates the blood‐testis barrier via disturbing occludin/ZO‐1 association and actin organization Besides as a monitor for Sertoli‐germ cell junction integrity, testin is also an essential molecule to maintain Sertoli–Sertoli junctions.